Systemic S100A8/A9 in patients with moderate to severe acute ischemic stroke: Exploratory analysis of inflammation and functional outcome - Christoph Vollmuth; Felipe A. Montellano; Cornelia Fiessler; Fabian Essig; Christian Hametner; Alexander M. Kollikowski; Vivian Vogt; Mirko Pham; Peter U. Heuschmann; Karl Georg Haeusler; Guido Stoll; Hermann Neugebauer; et al. (Brain, Behavior, & Immunity - Health)
Introduction: S100A8/A9, a danger-associated molecular pattern (DAMP), is released from leukocytes, mainly neutrophils, and augments inflammation and tissue damage. The role of systemic plasma levels of S100A8/A9 in stroke-related inflammation and its association with clinical outcome lacks sufficient data. Methods: Prospective, monocentric, observational study including patients with moderate to severe acute ischemic anterior circulation stroke [National Institutes of Health Stroke Scale (NIHSS) score ≥6 points and/or mechanical recanalization)]. We assessed functional outcome by telephone interview 3 months (±14 days) after stroke using the 7-point modified Rankin Scale (mRS). Poor outcome was defined as mRS ≥3. Systemic plasma levels of S100A8/A9 were determined by ELISA <48 h after onset of symptoms, alongside a differential blood count. Univariable and multivariable logistic regression were performed to investigate the association between systemic plasma levels of S100A8/A9 and functional outcome. Results: Between June 2020 and September 2022, a total of 272 patients were enrolled [52 % female, median age 79 years (IQR: 66–84), median NIHSS score on admission 13 (IQR: 8–17), median ASPECTS 8 (IQR: 6–9)]. Of these, 220 patients (81 %) underwent mechanical recanalization, and 118 (43 %) received systemic thrombolytic therapy. There was a significant correlation between systemic plasma levels of S100A8/A9 and neutrophil counts at baseline [p < 0.0001; r = 0.33 (95 % confidence interval: 0.22; 0.44)]. At 3 months, 192 of 272 (71 %) patients had poor functional outcome, who had significantly higher systemic plasma levels of S100A8/A9 at baseline [median: 525 ng/ml (IQR: 342–897)] than those with good functional outcome [397 ng/ml (IQR: 232–580); p = 0.001]. Furthermore, systemic plasma levels of S100A8/A9 at baseline were associated with poor outcome [unadjusted odds ratio (OR): 2.01 (95 %CI: 1.04–3.96)], however this association was attenuated and no longer significant when adjusting for age, sex, NIHSS Score on admission, ASPECT Score on admission and recanalization therapy (yes/no) [adjusted OR: 1.92 (95 %CI: 0.86–4.34)]. Conclusions: Systemic plasma levels of S100A8/A9 were associated with poor outcome in patients with moderate to severe ischemic stroke. The observed correlation with neutrophil counts at baseline might underscore an important pathophysiological link between patients’ prognosis and stroke-related inflammation. Study registration: DRKS00022064.